Change Resistance and Clinical Practice Strategies in Audiology - Wince, Jessica R.; Emanuel, Diana C.; Hendy, Nhung T.; Reed, Nicholas S. (Journal of the American Academy of Audiology, 2022)
Background Audiology is experiencing pressure from market forces that may change the profession's nature. Research suggests that understanding resistance needs to change and organizational culture may provide insights that can facilitate change.Purpose This study was designed to examine audiologists' resistance to change, organizational culture, and clinical practices related to hearing aid pricing and audiology assistants.Research Design This study utilized a cross-sectional and nonexperimental survey design.Study Sample Participants were 205 U.S. audiologists, representing diversity across experience, work setting, and location.Data Collection This survey examined demographics and clinical practice strategies. Resistance to change (RTC) scale examined disposition toward change. Organizational culture profile (OCP) examined organizational culture perspectives.Results The majority (52%) of respondents use bundled pricing but 42% of these repondents anticipate transitioning to unbundling. Use of hybrid pricing is increasing. Service-extender personnel were reported by 41%. Although the majority (66%) do not work with audiology assistants currently, 32% of these participants anticipate they will do so in the future. Results indicated lower RTC and greater years of experience were associated with more positive perceptions about organizational culture. Pricing structure was related to experience.Conclusion Trends indicate use of bundled pricing is decreasing, use of hybrid pricing is increasing, and employment of audiology assistants is increasing. Experienced audiologists are more likely to report unbundled and hybrid pricing compared with less experienced audiologists.
Keywords: audiologist; resistance to change; organizational culture